If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x = 4x + -24 Reorder the terms: x = -24 + 4x Solving x = -24 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. x + -4x = -24 + 4x + -4x Combine like terms: x + -4x = -3x -3x = -24 + 4x + -4x Combine like terms: 4x + -4x = 0 -3x = -24 + 0 -3x = -24 Divide each side by '-3'. x = 8 Simplifying x = 8
| .5a(x-5)=36 | | f(-3)=3x^2-x | | .5a+5=36 | | 3sinx-4sin^3x=1-2sin^2x | | .25x+5=36 | | .25(x+5)=36 | | .25(x-5)=36 | | .25x=36+5 | | 3(1-6x)=147 | | 7(1x+7)=77 | | -0.01x^2+0.26x+7.60=9.2 | | 2x+5+31=4x-10 | | 7x+2=6x+11 | | 44=4x+3x+9 | | 20z^2+21z+4=0 | | 5(2+u)-x=10+4(x+1) | | 2x+(-18)=3 | | 10p+12q=84 | | 5(4x-5)-4x-3=-124 | | 2(m+7)=70 | | 5.25s-2.01=-894 | | -6(1+3x)=84 | | 3+lnx=6 | | 2x+(-9)=3 | | -9x-10=-5x+22 | | 16x^2-39.2x+98=0 | | -3.3+8.6= | | -9-10=-5x+22 | | 2013x=0 | | 5x+5x=3x+8+3x+2 | | -16t^2+116t+c=0 | | 2*5x=3x+8*2 |